Design and application of a borehole–surface microseismic monitoring system. Issue 3 (4th May 2017) - Zhu, Yadongyang; Li, Na; Sun, Feng; Lin, Jun; Chen, Zubin
ABSTRACT: Borehole–surface microseismic monitoring is a new approach for monitoring artificially induced hydraulic fracturing in an oil or gas field. However, ineffective communication links and incompatible data formats between current borehole- and surface-based monitoring systems mean that borehole–surface monitoring cannot be reported in real time. To solve this problem, the borehole–surface microseismic monitoring system reported here allows fracturing points through inversion and the development of fractures to be viewed in real time. Private cloud technology is used to control the instruments, manage the borehole and the surface database, and process the data. This system ensures high performance and availability of the system. The data acquisition modules and the geophones used in the borehole and surface instruments were calibrated in the laboratory to ensure the consistency of the acquired microseismic signals. The monitoring system located 82 microseismic events with a fracture azimuth of N84°E during fracture production in the Daqing Oilfield. Subsequent analysis showed that the locations of the fractures and their strike directions were consistent with the theory of hydraulic fracture propagation and the local crustal stress field. The results demonstrate that the monitoring system effectively and promptly processed data, thus enabling real-time borehole–surface microseismic monitoring.